Female Entrepreneurship Research: An Evolution of the Field and Impact on Policy - Akorige Atarah, Bede; Finotto, Vladi (Senate Hall, 2021)
This paper maps out female entrepreneurship research from 1986 to 2020, highlighting contributors to the field and the impact they have made, and exploring how researchers have considered the mediatory role of "motherhood" and "meso/macro environment" on female entrepreneurship in their research. Bibliometric methods using HistCite and VOSviewer analytical tools were used to conduct a performance analysis and science mapping of the female entrepreneurship literature. We looked at the evolution of the female entrepreneurship literature using the 5Ms framework as the guiding lamp. We discovered that female entrepreneurship research is fast-growing, but still predominantly carried out by female researchers. Our review also revealed that over the years, women's family context (Motherhood), i.e. the presence of young children and other family roles; and their environments (Meso/macro), i.e. expectations and cultural norms of female entrepreneurs set by society, mediate their ability to identify or create opportunities (Market), their access to financial capital (Money) and their ability to profitably run their ventures (Management). How female entrepreneurship research findings appear to influence public policy on female entrepreneurship is also considered. In particular, a comparison of policy documents between the OECD/EU and Ghana suggests that scientific findings from female entrepreneurship research play a bigger role in public policy making on female entrepreneurship in the developed country context compared to developing countries. Finally, the present study also proposes possible future directions of female entrepreneurship research.
Keywords: female entrepreneurship|public policy|5Ms framework